Strengthen the Community by Promoting Multilingualism and Cultural Diversity - Khasinah, Siti (Bansigom Na Publisher, 2024)
Promoting multilingualism and cultural diversity is a strategic investment in community resilience and prosperity. This study highlights the importance of embracing linguistic and cultural diversity to build stronger, more inclusive communities. Drawing on examples from Indonesia and Songkhla, Thailand, this paper demonstrates how multilingual education, cultural festivals, and language exchange programs foster social cohesion, economic growth, and intercultural understanding. Participants in the International Community Engagement Program (PKM) exhibited significant improvements in understanding these topics through interactive presentations and discussions. The positive feedback and active engagement during the program underscore its success in promoting a deeper understanding of the benefits of diversity. As Kymlicka and Banting (2006) argue, linguistic and cultural diversity are valuable assets that enhance community strength and resilience. By implementing inclusive policies and initiatives, communities can harness the full potential of their diverse populations, leading to sustainable development and social harmony. This discussion underscores the necessity of investing in diversity to create vibrant, dynamic, and resilient communities.